2012
DOI: 10.1590/s0103-507x2012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida prévia à internação em unidade de terapia intensiva

Abstract: ObjectiveTo examine the reliability of the SF-36 general health questionnaire when used to evaluate the health status of critically ill patients before admission to intensive care and to measure their health-related quality of life prior to admission and its relation to severity of illness and length of stay in the intensive care unit. MethodsProspective cohort study conducted in the intensive care unit of a public teaching hospital. Over three months, communicative and oriented patients were interviewed withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…In this paper, there was no significant relationship between the life quality of patients discharged from the intensive care unit and type of critical care unit and diagnosis (in terms of having trauma or not having trauma). Toein et al's study conducted in 2012 is parallel with this research, whereas Tereran's study is not (21,44). In Tereran's study, patients hospitalized in ICU were assessed based on internal, surgical, and general conditions, while they were not checked out based on having trauma or not having trauma, as well as the devastating mechanism.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this paper, there was no significant relationship between the life quality of patients discharged from the intensive care unit and type of critical care unit and diagnosis (in terms of having trauma or not having trauma). Toein et al's study conducted in 2012 is parallel with this research, whereas Tereran's study is not (21,44). In Tereran's study, patients hospitalized in ICU were assessed based on internal, surgical, and general conditions, while they were not checked out based on having trauma or not having trauma, as well as the devastating mechanism.…”
Section: Discussionmentioning
confidence: 84%
“…In 2013, Vainiola et al voiced the idea that the quality of life in patients who need to undergo surgical procedures is lower than in other patients. Whereas, Tereran et al (2012) reported that there is no significant association between the patients' life quality, type of critical care unit, and their diagnosis as traumatically and nontraumatically (21).…”
Section: Introductionmentioning
confidence: 98%
“…These data are similar to the characteristics of patients admitted in other ICUs of the country, where a predominance of male patients and mean age of 53.69 years, 55.8 years, and 60.0 years was observed. [21][22][23] Population aging in the country, resulting in an increased number of individuals with noncommunicable chronic diseases, leads to a higher level of vulnerability of older age groups and increases morbidity and the frequency of hospitalizations of elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is noteworthy that the higher the level of severity of the patient, the higher their level of dependence and length of stay in the intensive care unit. 21,25 High levels of severity increase the risk of healthcareassociated infections because patients are unstable, require invasive procedures, present longer length of stay in the ICU, and require insertion of multiple catheters and excessive manipulation of CVC lines. 25 A multicenter study evidenced that dressing disruption is a common event in ICUs.…”
mentioning
confidence: 99%
“…7 When it is referred to as health care, it is called" health-related quality of life, "thereby encompassing the level of well-being and satisfaction in an individual's life and how, from the perspective of the patient, he is affected by illnesses, accidents and treatments. 8 As therapy progresses in intensive care, overall mortality decreases, but ICU survivors experience increased morbidity and a worse functional prognosis. The hospitalization often results in kinetic-functional changes in the post-discharge period, which lead to the inability to perform certain activities, restricting social participation.…”
Section: Introductionmentioning
confidence: 99%